Systematic critical review of Risk Management in Malaysian construction companies - Omer, Manal Suliman; Adeleke, A. Q. (Al-Khindi, 2019)
In recent times, the Malaysian construction companies have been bedevilled by myriads of risk issues which have hampered their smooth operations. Emerging evidence has therefore revealed that the process of developing risk management is still at the primitive stage in many Malaysian construction companies. The need then arises for an adequate risk management study in order to curtail the inherent danger to the productivities of Malaysian construction company. The application of an effective risk management helps in the improvement of performance of any project with respect to the tripods of cost, time and quality. The paper follows an earlier work published by many researchers in which the authors analyzed the global construction industry with focus on the evolution of risk management. The future of construction is exciting in which international markets; technological innovations, and construction project management techniques and new relationships across disciplines, are all avenues for development. To make the best use of the opportunities, the MCI must invest in research and development (R&D), undertake public education about the field and develop new methodologies to improve operational performance in construction. This study proposed future direction in the management of some selection risk using a systematic review of related researches